Intradermal Rabies Vaccination: Improved Economical Regimen - Shah, Venu; Shethwala, Nimisha; Fancy, Manish; Bala, D V (National Journal of Community Medicine, 2011)
Rabies is the communicable disease which is 100% fatal. However, it is 100% preventable with timely and accurate post exposure prophylaxis. Ahmedabad Municipal Corporation is one of the selected cities in the pilot project on Prevention and Control of Human Rabies 2008–2010 that by National Center for Disease Control (NCDC), New Delhi. One of the objectives of this project is to give Anti-Rabies Vaccine (ARV) by Intra-dermal (ID) route. Present study has been carried out in ARV Clinic of V S General Hospital. Forty randomly selected animal bite cases have selected. Written consent was taken after explaining about the study and serum sample was collected on day 28 from each one of the 40 patients who have received all scheduled doses of Intra-dermal rabies vaccine. Serum samples were sent to NCDC, New Delhi for estimation of antibody titers. Adequate number of antibodies (i.e.>0.5I.U./ml) were observed in 37(92.7%) samples.